2006
DOI: 10.1111/j.1365-2842.2005.01591.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of the biocompatibility of three current bonding agents

Abstract: summary  The aim of this in vivo study was to evaluate the biocompatibility of three current bonding agents and calcium hydroxide cement. Sixty polyethylene tubes filled with the following materials: Group 1: Prime & Bond NT (PB – Dentsply, US; Group 2: Bond 1 (BO – Jeneric/Pentron, US); Group 3: Optibond Solo (OP – Kerr, US); and Group 4 (control): calcium hydroxide cement – Dycal (CH – Dentsply, US) were implanted into the connective tissue of 30 rats. After 15, 30 and 60 days, the implants were excised and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…Several studies have evaluated in vivo biocompatibility of different dental materials by implantation techniques [114,115,116,117,118,119]. …”
Section: Local Adverse Reactions and Evaluation Systemsmentioning
confidence: 99%
“…Several studies have evaluated in vivo biocompatibility of different dental materials by implantation techniques [114,115,116,117,118,119]. …”
Section: Local Adverse Reactions and Evaluation Systemsmentioning
confidence: 99%
“…24,25 Moreover, in uncured state, HEMA quickly absorbs water from dentin compromising the degree conversion. 26 Consequently a poor quality polymer network with weak mechanical properties will be formed.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, studies on the long-term clinical performances of protective liners or bases are lacking, 2,12 and there are currently very few in vivo references for the biocompatibilities of different dentin-bonding systems. 13,14 Initially, we carried out an assessment of composite resin restorations for tooth sensitivity using three criteria, spontaneous pain, thermal sensitivity, sensitivity to percussion, at 7 days after the placement of restorations. 15,16 The results showed that short-term pulp complications were more effectively prevented with self-etching adhesive systems than with conventional pulp protection, and that cavity depth and the type of dentin-bonding system were contributory factors in the occurrence of short-term pulp complications.…”
Section: Introductionmentioning
confidence: 99%